PTU-141 Bile acid malabsorption: an evaluation of current practice. (28th May 2012) - Hashim, A; Paulon, E; Ahmed, M
Abstract : Introduction: Primary or idiopathic bile acid malabsorption (BAM) is increasingly recognised as a cause of chronic diarrhoea. Nevertheless, it remains underestimated by many gastroenterologists partly because of the limited use of the gold standard SeHCAT test. We aimed to determine the prevalence of primary bile acid malabsorption and the duration of diarrhoea in this category of patients. We also compared our current practice of BAM detection using SeHCAT with the British Society of Gastroenterology (BSG) guidelines for the investigation of chronic diarrhoea. Methods: This is a retrospective evaluative study of chronic diarrhoea patients who underwent a SeHCAT test between January and October 2011. The study was undertaken at the BHRU Hospitals in Greater London, UK. A total coverage sample was obtained and data were retrieved from the local patient electronic records. Results: The total number of patients who received SeHCAT was 47, of which 5 had to be excluded because of unavailability of the patients notes. Of the remaining 42 patients, 60% (25) had a positive SeHCAT test indicating significant bile acid malabsorption. To facilitate further analysis the study population was subcategorised into patients who had Crohn's disease (24%), cholecystectomy (33%), gastric bypass (2%), IBS (10%) and unexplained diarrhoea (31%). Idiopathic bile acid malabsorption was detected in 19% (8) of the general study population, 25% of IBS patients and in 54% of those with unexplained diarrhoea. The mean duration of diarrhoea was 5.1 years in the total population with similar figures (4.6 years) among the subcategory of patients with idiopathic bile acid malabsorption. On comparison with the BSG, we found that only 76% and 71% had their haematenics and coeliac screening checked respectively. The latter is specifically relevant to the subject as coeliac disease may interfere with bile acid metabolism. The study also revealed that 90% (38) of our study population had colonoscopy. Twelve out of 14 patients aged <45 years with no other indication for colonoscopy, received full colonoscopy. Although this is considered safe, it carries cost implications as the BSG suggests flexi-sigmoidoscopy alone for this group of patients, Conclusion: The study revealed a high prevalence of idiopathic BAM in the study population and even higher among those who had IBS/unexplained diarrhoea. The results also showed a long average duration of diarhoea before a solid diagnosis of primary BAM was established. We therefore, recommend early consideration of BAM in all patients with unexplained chronic diarrhoea. The SeHCAT test is a safe, non-invasive, and cheap investigation and should be more widely used by gastroenterologists. However, initial basic diarrhoea investigations must be offered to all patients to avoid under-diagnosing other common conditions. Competing interests: None declared.